2005
DOI: 10.1370/afm.364
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Goal Setting to Improve Lifestyle Behaviors: Lessons Learned From NOPCRN

Abstract: PURPOSEW e examined the effectiveness of a multicomponent lifestyle activity intervention for overweight or obese patients with impaired fasting glucose (prediabetes). The physician-directed counseling intervention included collaborative goal setting with patients to achieve specifi c changes in physical activity and nutrition behaviors. Nurse surveillance was used to provide reinforcement and to monitor progress. METHODSWe randomized 88 adult patients with prediabetes and a body mass index of 25 kg/m 2 or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Weekly goal-setting is another key aspect of OPTIMAL and each week participants set realistic and achievable goals to work on over the following week. Goal-setting has been shown in previous studies to be an effective mechanism to enhance self-management strategies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weekly goal-setting is another key aspect of OPTIMAL and each week participants set realistic and achievable goals to work on over the following week. Goal-setting has been shown in previous studies to be an effective mechanism to enhance self-management strategies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only intervention physicians received brief education regarding weight-related counseling focused on electronic tool usage; however, prior studies have demonstrated that brief educational sessions in isolation from systemic supports have minimal impact on physician counseling patterns. [29][30][31] Attitudes of intervention physicians who did not use the tools are not known since these individuals did not complete the survey. We did not review all available charts due to time and resource limitations; our sample size was adequately powered to detect a significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Time constraints faced by physician providers necessitate greater reliance on nurses and MAs [ 24 ]. Furthermore, evidence suggests health behavioral change interventions are more effective when allied health personnel are trained to augment physician brief counseling and education efforts [ 46 - 49 ].…”
Section: Discussionmentioning
confidence: 99%